2021
DOI: 10.1103/physrevb.104.054116
|View full text |Cite
|
Sign up to set email alerts
|

Modulated crystal structure of the atypical charge density wave state of single-crystal Lu2Ir3Si5

Abstract: The three-dimensional charge density wave (CDW) compound Lu 2 Ir 3 Si 5 undergoes a first-order CDW phase transition at around 200 K. An atypical CDW state is found, that is characterized by an incommensurate CDW with q = [0.2499(3), 0.4843(4), 0.2386(2)] at 60 K, and a large orthorhombic-to-triclinic lattice distortion with β = 91.945(2) • . We present the modulated crystal structure of the incommensurate CDW state. Structural analysis shows that the CDW resides on the zigzag chains of iridium atoms along c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…Just as in the case of R 2 Ir 3 Si 5 ( R = Lu, Er), , we observe that the electrical resistivity exhibits a T 2 dependence below T = 50 K, which is up to much higher temperatures than ∼10 K to be associated with Fermi-liquid behavior, implying dominant contributions from short-range magnetic fluctuations of Ho spins in the absence of long-range magnetic ordering.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Just as in the case of R 2 Ir 3 Si 5 ( R = Lu, Er), , we observe that the electrical resistivity exhibits a T 2 dependence below T = 50 K, which is up to much higher temperatures than ∼10 K to be associated with Fermi-liquid behavior, implying dominant contributions from short-range magnetic fluctuations of Ho spins in the absence of long-range magnetic ordering.…”
Section: Resultssupporting
confidence: 70%
“…Analysis of the modulation amplitudes and distances revealed that Ho 2 Ir 3 Si 5 follows a similar pattern as R 2 Ir 3 Si 5 ( R = Lu, Er), , such that the CDW resides on zigzag chains of Ir1a–Ir1b atoms, as they have the shortest metal–metal distances and exhibit the largest modulation of these distances (Figure )­. The lattice distortion results in alternating short and long Ir1a–Ir1b distances, where the shorter distance is the most affected by the modulation.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This behaviour is in contrast to other CDW materials, like Er 2 Ir 3 Si 5 , Lu 2 Ir 3 Si 5 and BaFe 2 Al 9 , for which the CDW transitions are accompanied by large lattice distortions (Ramakrishnan et al, 2020(Ramakrishnan et al, , 2021Meier et al, 2021).…”
Section: Introductioncontrasting
confidence: 69%
“…This feature might explain why the lowering of symmetry has not been found in earlier studies on EuAl 4 . This behavior is in contrast to other CDW materials, like Er 2 Ir 3 Si 5 , Lu 2 Ir 3 Si 5 and BaFe 2 Al 9 , for which the CDW transitions are accompanied by large lattice distortions (Ramakrishnan et al, 2020;Ramakrishnan et al, 2021;Meier et al, 2021) The phenomenon of CDW was originally identified as a property of crystals with quasi-one-dimensional (1D) electron bands, such as NbSe 3 and K 0.3 MoO 3 (Gruner, 1994;Monceau, 2012). A CDW is formed due to Fermi surface nesting (FSN), where the nesting vector of the periodic structure becomes the wave vector of the CDW of the metallic bands as well as of the accompanying modulation of the atomic positions (periodic lattice distortion-PLD).…”
Section: Introductionmentioning
confidence: 65%